STRATEGIC PEDAGOGICAL FRAMEWORK FOR TEACHING ONOMASTIC UNITS THROUGH LINGUOCULTUROLOGICAL INTEGRATION IN ENGLISH AND UZBEK CONTEXTS - Mamatkulova Bakhtijon Ravshanovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article proposes a strategic pedagogical framework for teaching onomastic units in English and Uzbek languages through linguoculturological integration. It focuses on the didactic potential of proper names as cultural markers and tools for developing intercultural awareness. The study introduces innovative strategic models, including discourse-based instruction, project-oriented learning, and cognitive-linguistic analysis. The results indicate that strategic incorporation of onomastic material into language teaching enhances learners’ pragmatic competence and cultural literacy. The paper also outlines practical classroom strategies and assessment tools for effective implementation.